TRADISI KEBERAGAMAAN SYI`AH FÄ€á¹¬IMIÄªYAH DI KOTA PALU - Soraya Attamimi (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) UIN Datokarama Palu, 2015)
This research focuses on religious tradition of Syi`ah Faá¹imiyah at Palu City. The objective is to know the historical present of Syi`ah Faá¹imiyah at Palu City, the procession to be its congregation, and reveal of religious tradition which run by them.This research was qualitative research design which used phenomenology approach. The population used was the congregation of Syi`ah Faá¹imiyah at Palu city taken the sample randomly. While the data collection was observation, interview and document study. The result of the research showed that the existence of Syi`ah Faá¹imiyah at Palu city has been here for long time, coincide with the merchant of India. The followers of Syi`ah Faá¹imiyah at present consisted of the society of India generation and the people who make a relationship with them through marriage. In some countries, Syi`ah Faá¹imiyah has been known as Syi`ah Dawoodi Bohra. The religious tradition followed by the followers of Syi`ah Faá¹imiyah bases on their demand of teaching. Even the tradition has been passed along the way from the original, but it hasn`t been changed the tradition of society. In some cases of religious tradition, Syi`ah Faá¹imiyah has the similarity with Syi`ah ImÄmÄ«yah IÅ›na á¼‰shariyah, such as á¼‰shÈ—ra, Arbaâ€˜in and Haul, so on. On the other side, it has similarity much with Ahlu Sunnah wa al-JamÄ`ah. However, in some cases it has basic difference, which seen from the faith of the tradition base